Human rights and development: the advancement of new campaign strategies. Issue 5 (28th May 2019) - Miller, Hannah
ABSTRACT: Contemporary scholarship has overwhelmingly focused on 'rights-based approaches' (RBAs) to development as being the principle way that development and human rights have merged in NGO practice. This article focuses on development-orientated campaign strategies, and in so doing challenges the ongoing RBA fixation by considering two praxis developments: (1) despite firm rejections of RBAs, alternative human rights strategies are being embedded in contemporary NGO practice, and; (2) over the past six years key changes in wider NGO campaigning contexts and environments have led to a further development in human rights approaches. Drawing on empirical findings from a ten-year in-depth research project on NGO practice, this article not only tracks developments in campaign practice, but also proposes two new models for consideration. These models – 'rights-framed' and 'rights-referenced', as practiced by influential NGOs – offer an innovative, strategic and instrumental embedding of a human rights discourse and practice.